2009
DOI: 10.1371/journal.pone.0008104
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ubiquitin-Ligase Bmi1/Ring1A Controls the Proteasomal Degradation of Top2α Cleavage Complex – A Potentially New Drug Target

Abstract: BackgroundThe topoisomerases Top1, Top2α and Top2β are important molecular targets for antitumor drugs, which specifically poison Top1 or Top2 isomers. While it was previously demonstrated that poisoned Top1 and Top2β are subject to proteasomal degradation, this phenomena was not demonstrated for Top2α.Methodology/Principal FindingsWe show here that Top2α is subject to drug induced proteasomal degradation as well, although at a lower rate than Top2β. Using an siRNA screen we identified Bmi1 and Ring1A as subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
79
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 43 publications
9
79
0
Order By: Relevance
“…29 However, in agreement with various reports showing that Bmi1 is the rate-limiting factor in the ubiquitination reactions mediated by the Ring proteins, 28,29 we demonstrated that Bmi1 overexpression or knockdown was sufficient to, respectively, induce or inhibit p53 polyubiquitination and regulate p53 stability. In vitro, we showed that Bmi1 strongly increased both Ring1A-and Ring1B-mediated p53 mono-and di-ubiquitination, thereby suggesting that an E4 enzyme is necessary in vivo for the elongation of the ubiquitin chain primed by these two E3 ligase complexes, as previously shown for MDM2-mediated p53 polyubiquitination.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…29 However, in agreement with various reports showing that Bmi1 is the rate-limiting factor in the ubiquitination reactions mediated by the Ring proteins, 28,29 we demonstrated that Bmi1 overexpression or knockdown was sufficient to, respectively, induce or inhibit p53 polyubiquitination and regulate p53 stability. In vitro, we showed that Bmi1 strongly increased both Ring1A-and Ring1B-mediated p53 mono-and di-ubiquitination, thereby suggesting that an E4 enzyme is necessary in vivo for the elongation of the ubiquitin chain primed by these two E3 ligase complexes, as previously shown for MDM2-mediated p53 polyubiquitination.…”
Section: Discussionsupporting
confidence: 91%
“…Bmi1 directly binds p53 and induces p53 polyubiquitination Bmi1 is known to enhance the E3 ubiquitin-ligase activity of Ring1A and Ring1B, and control the proteasomal degradation of a non-histone protein, topoisomerase 2a, 28 indicating that the Bmi1-induced phenotype can be mediated via mechanisms that do not involve transcriptional regulation. Consequently, we examined whether Bmi1 could bind p53 and directly induce its polyubiquitination.…”
Section: Mycn Protects Neuroblastoma Precursor Cells From Death Stimulimentioning
confidence: 99%
“…4A) (Guenatri et al, 2004). Chromatin immunoprecipitation (ChIP) in control cells showed H2AK119Ub enrichment at these domains, but it was wiped out in mutant cells after only 48 h of treatment, in agreement with the highly dynamic turnover of this histone mark (Alchanati et al, 2009). In addition, we also found RING1B occupying major satellites in control cells (Fig.…”
Section: Ink4amentioning
confidence: 64%
“…In this study, we have characterized PRT4165, a small molecule identified in a screen for inhibitors of BMI1/RING1A-mediated polyubiquitylation of topoisomerase II-␣ upon trapping the DSB intermediate with the topoisomerase II inhibitor etoposide (7). We demonstrate that PRT4165 inhibits the two E3 ligase paralogues, RING1A and RNF2, in vitro, and that it can be used to inhibit H2A ubiquitylation in cells.…”
Section: Discussionmentioning
confidence: 96%
“…This inhibits ubiquitylation at DSBs by sequestering ubiquitin in the cytoplasm in lysine 48-linked polyubiquitin chains (6). Recently, an inhibitor of BMI1/RING1-mediated polyubiquitylation of topoisomerase II was identified (7). BMI1/RING1 are subunits of the polycomb repressive complex 1 (PRC1) (8,9).…”
mentioning
confidence: 99%